Influence of Different Biomolecules on Crystal Growth of Calcium Oxalate in Microemulsion - Yue, Wenjin; Nie, Guangjun (Asian Journal of Chemistry, 2010)
Crystal growth of calcium oxalate in reverse microemulsion of p-octyl polyethylene glycol phenylether (op)/iso-octyl alcohol (IOA)/cyclohexane/ water and above microemulsion containing different biomolecules, such as protease, glucan, carboxyl methyl chitosans were studied. Calcium oxalate crystals were characterized by transmits electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) spectrum. The results indicated that different crystallization types of the crystals, which were calcium oxalate monohydrate (COM), calcium oxalate dihydrate (COD) and calcium oxalate trihydrate (COT),existed in reverse microemulsion, while protease promotes the formation of COM, glucan and carboxyl methyl chitosans could promote the formation of COT, especially is carboxyl methyl chitosans. It could prohibit the formation of COM, COD strongly. These facts suggested that different biomolecules promote crystal growth of different calcium oxalate hydrate selectively. Furthermore, it could be concluded that carboxyl methyl chitosans may be depressor of urinary stone in future.